SOME DENSITY PROFILES OF AN INHOMOGENEOUS SCHRöDINGER EQUATION - T. B. Prayitno (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
We provide some density profiles of an inhomogeneous Schrödinger equation by giving some available functions representing the inhomogeneous term. The inhomogeneous Schrödinger equation, which is achieved by reducing a set of two-coupled Gross-Pitaevskii equations, describes a motion equation of a weakly outcoupled atom laser inside the condensate zone. In this case, to attain the density profile we use the separation of variables in order to simplify our calculation.Keywords: density profile, atom laser, Schrödinger equation.